Development of 21st Century Skills Through Steam PJBL in The Topic of Salt Hydrolysis and Buffer Solutions - Lisdiana, Hayyun; Rahmawati, Yuli; Ridwan, Achmad; Hadinugrahaningsih, Tritiyatma (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2023)
Globalization influences various aspects, including education, so learning is needed to improve skills and quality of life abilities. This research aims to develop 21st-century skills through project-based learning (PjBL) and STEAM (Science, Engineering, Technology, Art, and mathematics). Participants in this study were 40 students in eleventh grade in the science program. This study used qualitative methods, which focused on the integration and implications of PjBL with the STEAM model on salt hydrolysis and buffer solutions. The STEAM project is a mockup of electrical conductivity and water purification on salt hydrolysis and hydroponic plant cultivation for projects on buffer solution—data collection techniques through interviews, reflective journals, classroom observations, and teacher diaries. The results showed that students were interested and motivated in making STEAM projects. 21st Century skills consisting of life and career skills can be seen from the initiative and a sense of responsibility in doing projects, learning and innovating skills seen from student creativity and innovation, and technology skills seen through marketing project creative ideas through information media and technology. Other implications, such as curiosity, motivation, and confidence, arise in the learning process. Based on its integration and implications, the STEAM approach with PjBL can be used as an alternative to improve 21st-century skills in chemistry learning